The clients’ assessment on the effectiveness of revenue collection strategies in improving revenue performance: A case study of Zimbabwe Electricity Transmission And Distribution Company (ZETDC) Northern Region - Wurayayi, S. (BUSE, 2022)
Modernizing and developing effective strategies in revenue collection has been a pivotal matter in revenue collection and reduction of debtors balances in the electricity sector or industry globally. The adoption of new and better strategies helps an organization to work more efficiently as well as collecting revenue which is needed to run the utilities on a day to day basis as well as financing capital projects. The importance of liquidity culminated in the current research on the effectiveness of revenue collection strategies as ZETDC Northern Region. ZETDC Northern Region embarked on a serious drive to collect revenue through adopting strategies on its main operations across the region. Innovative and modern revenue collection strategies implemented were supposed to improve organizational structure, training, manpower planning, developing team work among management and staff. The purpose of the study was to assess the clients’ assessment on effectiveness of revenue collection strategies in improving revenue performance at ZETDC Northern Region. The objectives of the research was to find out the collection strategies in place, assess effectiveness of the strategies and propose possible new collection strategies. A descriptive research method was used focusing on qualitative characteristics and status of the vast revenue collection strategies employed by ZETDC Northern Region in improving the revenue performance. ZETDC Northern Region has 800 employees and 145000 clients. The focus was on 20 credit control staff, 18 Customer service officers as well as 13 management staff. A purposive and expert sampling method was employed in this study to select a sample of 24 employees. Data was also collected from registered clients with the view of getting independent comments on better ways of collecting revenue. A sample of 32 clients was chosen with fair representation from each tariff category. In this study, data was collected using structures and open ended questionnaires administered through face to face interactions and emails for those geographically far away. Data was analyzed using a thematic and content analysis to discover emerging major views regarding the effectiveness of revenue collection strategies of ZETDC. Firstly, data was collected, cleaned, sorted and collated. Data matching and coding was done to maintain the temporary employees’ confidentiality. Then, it was entered in a computer, after which analysis was done. Descriptive statistics in the form of pie charts, contingency tables and bar graphs were used to describe the data. Then measures of association were used to examine the relationship between the independent and dependent variables. The major findings were that effective power disconnection improves revenue collection paired with full adoption of performance based contracts. It was further deduced that staff plays a key role along revenue collection value chain hence the need to train staff to equip and capacitate them with requisite skills. Monitoring and evaluation was identified as a weak link in the revenue collection value chain and improvement as well as establishment of the same will significantly add to revenue collection. Business process were recommended for automation, staff capacitated with skills like communication, negotiation and customer care with the view of motivating clients to pay before adoption of other harsh credit control measures. In conclusion, it was shown that there is a positive correlation between independent variables which are revenue collection strategies and dependent variable which is revenue collected owing to the role which the strategies play in enhancing revenue collection and reduction in debtors.
Keywords: revenue collection; debt; debtors; electricity; ZETDC; Northen Region; strategies